Managing Tomato Fruit Flies (Atherigona orientalis) Alphacypermethrin and Basil Extract Mardan Khyber - Pakhtunkhwa, Pakistan - Khan, Fawad; Mahnoor Pervez; Farman Ali (Andalasian International Journal of Entomology, 2025)
Tomato (Lycopersicon esculentum) is one of the most widely grown vegetables globally. Integrated pest management, which combines multiple control methods, is commonly used to tackle fruit fly infestation. The experiment conducted at Abdul Wali Khan University Mardan, Pakistan in 2022, evaluated the efficacy of Alphacypermethrin, Basil Extract, and a Control treatment against Atherigona orientalis in tomato cultivation. Using a Randomized Complete Block Design (RCBD) with five replicates, the study assessed the effects of these treatments on pest populations and tomato yield. Alphacypermethrin proved to be the most effective in reducing larval, pupal, and adult infestations, leading to a significant increase in healthy fruit yield. Basil Extract showed moderate effectiveness, while the Control treatment exhibited higher infestation rates and lower yield. These findings suggest Alphacypermethrin as a reliable pest control agent, with Basil Extract as a sustainable alternative or supplementary option within Integrated Pest Management (IPM) strategies. Future work should explore the integration of both treatments and evaluate their long-term environmental impacts.